The Montgomery Bus Boycott - Walsh, Frank (Milwaukee, Wis. : World Almanac Library, 2003)
This book describes how the black community of Montgomery, Alabama, staged the 1955 boycott to end segregation on public buses.
Includes index.
Includes glossary.
Includes bibliography.
4-8
Keywords: Segregation in transportation -- Montgomery (Ala.) -- History; African Americans -- Civil rights -- History; Montgomery (Ala.) -- Race relations